Knowledge And Attitudes Of Dental Students Toward Virus Infections: A Study at The Universitas Syiah Kuala Dental and Oral Hospital - Yuli Fatzia Ossa; Vera Yulina; Nuzulul Ismi (Universitas Syiah Kuala, 2024)
Oral manifestation of viral infections has similar clinical appearances. This study aims to determine the knowledge and attitudes of dental students in recognizing virus infections. A cross-sectional study was conducted on 205 clinical dental students of Universitas Syiah Kuala in 2022 with a questionnaire consisting of demographic data, etiology of viral infections, oral manifestation, clinical photos of lesions, and attitude toward infection control procedure. Results show that almost all knew the etiology of herpes labialis (92.7%), but not the etiology of herpangina and hand-foot and mouth disease. The respondents did not know that clinical photos of stomatitis aphthous recurrent major (52.7%), oral hairy leukoplakia (52.7%), and pseudomembranous candidiasis (62.4%) were not virus infections. The vaccination status of respondents was 37.6% of respondents who had been fully vaccinated against COVID-19, and 33.7% had a hepatitis vaccine. Most of the respondents have applied the principle of universal precautions when working with patients. In conclusion, the knowledge level of respondents in recognizing the etiology, and oral manifestations of viral infection is good, however, the ability to recognize clinical photos is low. Self-protection from viral infections is low based on vaccination status, and attitudes toward self-protection when practice is already good. Dental students need to learn more about viral infections related to oral cavities so that they become more skilled in treating patients with viral infections.